Bibliometric Analysis on the Implementation of Heutagogy and Cybergogy in Inclusive Education for Higher Education - Jatiningsiwi, Tata Gading; Ummah, Umi Safiul; Zainal, Mohd Syazwan Bin; Kawai, Norimune; Cheong, Loh Sau; Low, Hui Min (Angstrom Centre of Education, 2025)
Inclusivity in education has become the worldwide for over 30 years, including in Indonesia. The models of learning became important to achieve learning goals. But, limited literature examines the implementation of heutagogy and cybergogy theories in learning models for higher education in inclusive settings. This study aims to examine how heutagogy and cybergogy theoretical approaches can be associated with inclusive education for higher education. The method used was bibliometric analysis. After filtered, 79 articles were found between 2019-2024, and they will be analyzed using performance analysis, science mapping, and visualization. The findings show that the implementation of heutagogy and cybergogy theories in inclusive education for higher education has not been widely studied. The research trends are around COVID-19, pedagogy, character education, and augmented reality. Further, only one study discusses the heutagogy approach to disability in higher education, but no study discusses the cybergogy approach to inclusive education in higher education, also no study discusses the approach through these two theories together in the practice of inclusive education for higher education.